Tom Smith's cricket umpiring and scoring : the internationally recognised definitive guide to the interpretation and application of the laws of cricket / [by Tom Smith and the Association of Cricket Umpires and Scorers] ; introduction by Richie Benaud. - Smith, T. E. (Thomas Edward), 1908- (Weidenfeld & Nicolson, 2004)
This is the only guide to the rules of umpiring and scoring authorised by the Association of Cricket Umpires & Scorers.